Assessing the Informative uses of Presuppositions and their Pragmatic Values - Francesca Ferrucci (Research Developments in Arts and Social Studies Vol. 2, 2022)
Previous research suggested the possibility of establishing systematic links between some intrinsic features of a presupposition and textual functions that it can carry out with greater probability. This study starts from an organic analysis of the semantics of presupposition triggers, thanks to a lexical database comprising 19,500 entries. The database was used to investigate a corpus of chat conversations that included about 200,000 tokens, with the general objective of exploring possible pragmatic values inside bidirectional interactions, thereby verifying the effects on the audience and the negotiation of the presupposed content. In the corpus, triggers mainly occur as noninformative, maintaining information already known by all those participating in the communication; but, depending on their different features, some of them are systematically associated to a function of anaphora and textual cohesion, while others strengthen social conventions and stereotypes. The informative uses, although in a minority proportion, are the most interesting category, where the presupposed content corresponds to the ’New’ in the Given/New dichotomy, thus generating a misalignment between what is actually implicit and what is conveyed as such. This misalignment appears to be an error in just a few cases and it corresponds to a low number of reader reactions: particular conditions in pragmatics and in the social context must be called into question to interpret the data.